2014
DOI: 10.1097/qai.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-Child Transmission of HIV in Kenya

Abstract: Background Kenya has an estimated 13,000 new infant HIV infections that occur annually. We measured the burden of HIV infection among women of childbearing age and assessed access to and coverage of key prevention of mother-to-child transmission interventions. Methods The second Kenya AIDS Indicator Survey was a nationally representative 2-stage cluster sample of households. We analyzed data from women aged 15–54 years who had delivered a newborn within the preceding 5 years and from whom we obtained samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 4 publications
1
26
1
Order By: Relevance
“…From our study, 72% of the HIV-positive pregnant mothers were on ART, which was comparable to the rate of 72% found in Kenya 12 and 82% found in Ghana. 13 The report by UNAIDS showed that, in 2013, only 68% of HIV-positive pregnant women in sub-Saharan Africa received ART.…”
Section: Discussionsupporting
confidence: 70%
“…From our study, 72% of the HIV-positive pregnant mothers were on ART, which was comparable to the rate of 72% found in Kenya 12 and 82% found in Ghana. 13 The report by UNAIDS showed that, in 2013, only 68% of HIV-positive pregnant women in sub-Saharan Africa received ART.…”
Section: Discussionsupporting
confidence: 70%
“…We found that initial HIV testing rates (98.0%) in our study were higher than the national average (93.1%), potentially due to a higher HIV prevalence in the region 9. In a recent meta‐analysis, Drake et al .…”
Section: Discussioncontrasting
confidence: 53%
“…The MTCT rate was estimated in 2012 to be 15%, accounting for 13,000 new childhood infections in Kenya annually 9, 10. In 2012, the Kenya Ministry of Health adopted international guidelines recommending that repeat HIV testing be offered three months after an initial negative HIV test result in early pregnancy 11.…”
Section: Introductionmentioning
confidence: 99%
“…6 Specific features of the PEARL community methodology allowed us to build upon their approach. Rather than relying on self-reported clinical outcomes, we collected and tested biological specimens from HIV-exposed infants and children, to ascertain HIV status at the time of the survey.…”
Section: Discussionmentioning
confidence: 99%
“…2 For example, in their recent report of the 2012 Kenya AIDS Indicator Survey (KAIS), Sirengo and colleagues assessed key steps along the PMTCT cascade using such cross-sectional individual-level information, including those who visited antenatal care during pregnancy, tested for HIV during pregnancy, initiated any maternal or infant prophylaxis, and reported an HIV-negative infant test 6 weeks after birth. 6 We sought to further refine this household survey approach using data from the PMTCT Effectiveness in Africa: Research and Linkages to Care (PEARL) study conducted in Zambia, South Africa, Cote d’Ivoire, and Cameroon. Our overall aim was to describe a monitoring framework to illustrate gaps in PMTCT service provision and their relative contribution to negative health outcomes among HIV-exposed infants.…”
Section: Introductionmentioning
confidence: 99%